Amitraz Poisoning Treatment: Still Supportive? - Eizadi-Mood, Nastaran (Shaheed Beheshti University of Medical Sciences, 2011)
Amitraz is a triazapentadiene, an α(2) adrenergic agonist and a member of the amidine chemical family. A limited number of human intoxication cases have been published in the literature. Lack of a clear and specific protocol for the therapy of amitraz intoxication may make its successfully managed case reports useful and valuable for other clinical practitioners in poisoning departments. The case is about a 22 years old female, single, university student, ingested a glass of amitraz poison (about 100 mL of a 20% solution) as a suicidal attempt on 11:30 am which was about 3.5 h before her hospital admission. She found nausea, vomiting, and dizziness. Immediately, her family took her to a clinic near their house. At that clinic (13:30 pm) she had miosis and they did gastric lavage , one adult dose of activated charcoal (50 g) and referred her to our Poisoning Emergency Department, where she was managed supportively and successfully. Amitraz is a poisonous chemical which may cause central nervous system depression and also respiratory/cardiovascular symptoms as well. Several studies reported that using atropine for those amitraz poisoned patients with both miosis and bradycardia resolved the problem and recommend it as the first line of drug therapy when bradycardia occurs from vagal stimulation and atrioventricular block. Management of amitraz poisoning is still considered to be supportive and symptomatic. Although the effects of activated charcoal and cathartics have not been studied, they may still be considered for treatment.